Live beautiful - Calderone, Athena (Abrams, 2020)
Beautiful design isn't just pleasant to look at; it improves the quality of our lives. It helps foster the traditions, rituals, and ceremonies we create in our homes. In Live Beautiful, the highly anticipated design book by Athena Calderone, the EyeSwoon creator taps into her network of interior decorators, fashion designers, and tastemakers to reveal how carefully crafted interiors come together. She also opens the doors to two of her own residences. With each homeowner, Calderone explores the initial spark of inspiration that incited the design journey and the deeply personal objects, stories, and references that accompanied it. She then breaks down the details of the rooms-like layered textures and patterns, collected pieces, and customized vignettes-and offers helpful tips and advice on how to bring these elevated elements into your own space. Filled with gorgeous photography by Nicole Franzen, Live Beautiful is both a showpiece of exquisite design and a guide to creating a home that's unique and thoughtfully put together.